Interseasonal effects of regulated deficit irrigation on growth, yield, water use, berry composition and wine attributes of Cabernet Sauvignon grapevines. (30th May 2013) - Edwards, E.J.; Clingeleffer, P.R.
Abstract Background and Aims Regulated deficit irrigation (RDI) has gained wide use in irrigated viticulture throughout the warm‐climate production regions of Australia. There has been, however, only limited study of the long‐term impact of RDI. This study aimed to determine if long‐term use of RDI impacted vine growth, harvest yield or berry composition. Methods and Results Mature Cabernet Sauvignon vines were irrigated in excess of crop evapotranspiration (control), with RDI and with an extended RDI strategy (prolonged deficit, PD). Growth of shoot and root was estimated, together with water use and yield. Fruit and wine composition were also determined. Irrigation treatment affected growth of canopy, trunk and roots, altered water use efficiency and impacted yield, and fruit and wine composition. Conclusions The use of RDI or prolonged deficit reduced yield relative to that of a well‐watered control, but the yield under deficit irrigation was stable over multiple seasons. Multiseason irrigation treatments resulted in interseasonal effects on vine growth, independent of the irrigation received within a given season. Significance of the Study Long‐term decline in vine productivity is unlikely to occur with continued use of RDI in warm‐climate viticulture, but the observed interseasonal impact on canopy growth highlights the limitation in our understanding of the mechanisms by which RDI controls vine vigour.